KEGAGALAN BAHASA SIMBOLIK DAN PEMBENTUKAN SUBJEKTIFITAS TERLUKA DALAM NOVEL PERANG KARYA RAMA WIRAWAN: KAJIAN PASCASTRUKTURALISME JULIA KRISTEVA - Ridwan; Nensilianti; Aliyah Rusyaehda Adnan (FRASA: Jurnal Keilmuan, Bahasa, Sastra, dan Pengajarannya, 2026)
This research begins with an attempt to understand how language is not always able to accommodate inner experiences, particularly in traumatic situations such as war. The focus of this study is to examine how the failure of symbolic language simultaneously shapes wounded subjectivity in Rama Wirawan's novel, Perang. Utilizing Julia Kristeva's poststructuralist perspective, the analysis focuses on the relationship between the symbolic and semiotic dimensions, the concept of abjection, and the notion of the subject in process. This research uses a qualitative descriptive method. The results indicate that the experience of war trauma causes symbolic language to lose its representational power; what the characters experience can no longer be fully expressed through structured language. In this situation, a semiotic overflow emerges in the form of emotions, rhythms, and expressions that feel linguistically "unfinished." As a result, the characters experience not only inner conflict but also alienation from themselves, which then forms a wounded subjectivity an incomplete identity that continually confronts traumatic memories. Through these findings, this research is expected to contribute to the study of literary psycholinguistics, particularly in understanding the complex relationship between language, trauma, and the formation of subjectivity.